Pesantren as a Pillar of Social Resilience: Islamic Education and Disaster Mitigation in East Java - Akhmad Sirojuddin; Devi Pramitha (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study aims to explore the role of Islamic education in pesantren in building social resilience in disaster-prone areas in East Java, Indonesia. Using a qualitative approach through case studies at three pesantren (Pesantren Ar-Rosyid, Pesantren Tangguh Bencana, and Pesantren Tebuireng), the research identifies how pesantren integrate Islamic values such as tawakkal (trust in God), sabar (patience), ukhuwah (brotherhood), and ta'awun (cooperation) into disaster mitigation and post-disaster social recovery activities. The empirical findings show that pesantren not only teach students mental and social resilience but also actively collaborate with the community and government in disaster recovery efforts. The findings highlight that pesantren play a central role in building strong social networks, which are crucial for accelerating post-disaster recovery. Pesantrens are also involved in disaster education, teaching practical skills and profound social values. These findings have practical implications for the development of faith-based disaster mitigation policies and the use of pesantren as strategic partners in disaster mitigation and recovery programs at both the local and national levels. This research also contributes to social resilience theory by adding a spiritual dimension and integrating religious values into community-based social resilience strategies.